2021
DOI: 10.1111/rda.13914
|View full text |Cite
|
Sign up to set email alerts
|

Bone morphogenetic protein 15 supplementation enhances cumulus expansion, nuclear maturation and progesterone production of in vitro‐matured bovine cumulus‐oocyte complexes

Abstract: In vitro embryo production (IVP) efficiency is reduced when compared to in vivo. The basic knowledge of bovine in vitro oocyte maturation (IVM) mechanisms provides support to improve in vitro embryo production yields. The present study assessed the effects of bone morphogenetic protein 15 (BMP15), fibroblast growth factor 16 (FGF16) and their combined action on cumulus cells (CC) expansion, oocyte and CC DNA fragmentation, oocyte nuclear maturation, energetic metabolism and progesterone production in bovine IV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Significantly more enlarged cumulus cells were found in the GC co-culture groups than in the control group, which may be explained by the increased BMP15 expression in oocytes. When BMP15 was added to the IVM medium, it also had a favorable effect on cumulus expansion in bovines ( Caixeta et al, 2013 ; Delgado et al, 2021 ). Moreover, null mutations in BMP15 in oocytes restrict follicular growth, indicating that paracrine factors influence cell viability, cumulus cell expansion, and metabolism during folliculogenesis ( Galloway et al, 2000 ; Su et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Significantly more enlarged cumulus cells were found in the GC co-culture groups than in the control group, which may be explained by the increased BMP15 expression in oocytes. When BMP15 was added to the IVM medium, it also had a favorable effect on cumulus expansion in bovines ( Caixeta et al, 2013 ; Delgado et al, 2021 ). Moreover, null mutations in BMP15 in oocytes restrict follicular growth, indicating that paracrine factors influence cell viability, cumulus cell expansion, and metabolism during folliculogenesis ( Galloway et al, 2000 ; Su et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some improvements to first polar body extrusion rates have been achieved by supplementation of IVM media with antioxidants melatonin, N-acetyl cysteine (NAC), mogroside V, putrecscine, β-cryptoxanthin, peroxiredoxin-4, and resveratrol [62][63][64][65][66][67][68]. Oocyte maturation rates in vitro were also improved by myostatin (alias GDF8) and bone morphogenic protein-15 (BMP-15), both of which are members of the TGFβ superfamily [69,70]. Increased rates of PB extrusion were also observed in IVM media supplemented with brainderived neurotrophic factor, all-trans retinoic acid, leptin, kisspeptin, AY 9944-A-7 (which promotes intrafollicular accumulation of follicular fluid meiosis activating sterol), and growth hormone [71][72][73][74][75][76].…”
Section: Pathways and Therapeuticsmentioning
confidence: 99%
“…GDF9 and BMP15 has an inhibitory effect on progesterone secretion in granulosa cells [21]. In a recent study, it was reported that BMP15 increased progesterone production by cumulus cells [22]. Both GDF9 and BMP15 can act as a potential biomarkers for the estimation of female infertility [23].…”
Section: 1mentioning
confidence: 99%